Bispro Students' Perceptions of the Satisfaction of the Teaching and Learning Process toward Strawberry Generation at the Bengkalis State Polytechnic - Halim Dwi Putra; Aswandi Aswandi (Journal Corner of Education, Linguistics, and Literature, 2023)
ABSTRACT The strawberry generation is the generation that was born after 2002. In that year, generally the generation is fragile, like a soft and easily crushed strawberry, which requires special specialization and treatment in the teaching and learning process in the English for business and professional communication (bispro) study program. The urgency of this research is to find out student feedback about perceptions and satisfaction with learning that has been carried out in the bispro study program at bengkalis state polytechnic towards educators to improve the quality provided. The methodology of this research is quantitative with 50 respondents who are categorized as a strawberry generation. The results of this study found that perception affected student satisfaction of 0.445. This can be interpreted as still low, so there needs to be an increase in the quality of lecturers and other support.